Exploring the potential of plant extracts in suppressing rice blast under field conditions - AAKASH; ASHWANI KUMAR; ANIL KUMAR SAINI; MAHAVEER SINGH BOCHALYA; POOJA; LOKESH YADAV (The Indian Journal of Agricultural Sciences)
Rice blast disease incited by Pyricularia oryzae, remains a substantial challenge in rice (Oryza sativa L.) cultivation, necessitating the exploration of management strategies. The present study was carried out during rainy (kharif) season of 2022–23 at Regional Research Station (Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana), Kaithal, Haryana to assess the efficacy of seven botanicals in controlling rice blast disease on two rice varieties, CSR 30 and PB 1121. The botanicals used for the study were, Neem leaf extract @ 20%; Garlic clove extract @10%; Ginger rhizome extract @10%; Turmeric powder extract @10%; Eucalyptus leaves extract @20% congress grass leaf extract @ 20% and Control. The experiment was laid out in randomized block design (RBD), replicated thrice with varied treatments. Among them, garlic clove extract followed by neem leaf extract found most effective reducing disease severity to 36.11% in PB 1121 and 37.96% in CSR 30 variety. On average, disease severity decreased to 41.11% in PB 1121 and 41.85% in CSR 30 variety with neem extract treatment. Eucalyptus leaves extract was found to be least effective in reducing leaf blast severity. Similar trend was observed in neck blast management. Garlic clove extract 31.11% in CSR 30 and 25.89% in PB 1121 proved most effective followed by neem leaf extract 35.56% in CSR 30 and 34.07% in PB 1121 and eucalyptus leaves extract (51.67%) found to be least effective. Similar trend was seen in terms yield for both the varieties. In conclusion, our study identifies garlic and neem extract as potent botanicals for effectively managing rice blast while simultaneously enhancing yield across varieties CSR 30 and PB 1121. These results signify the promising role of garlic and neem extract in sustainable rice cultivation, warranting further investigation and adoption in agricultural practices to promote disease resilience and productivity.